Elevating Student Engagement through Active Learning Strategy: An Exploratory Study of Instructional Management in State Islamic Junior High School - Muhammad Jikri; Najminnur Hasanatun Nida; Agustian Ramadana Putera (Universitas Cokroaminoto Palopo, 2023)
Many people assume that Islamic subjects are boring because the stereotype of Islamic education always emphasizes memorisation. This research aims to find out the stages of learning management in Islamic subjects using Active Learning Strategy (ALS) to stimulate student involvement in the classroom. The data collection methods used are observation of teachers to observe how the ALS process is implemented in the classroom, interviews with teachers regarding learning management, and documentation by looking at lesson plans that have been made by teachers. The study of MTsN 4 Barito Kuala in South Kalimantan province where this school has successfully integrated Islamic subjects, student involvement, and ALS. The results of this study are: 1) We can track all the teachers' planning through the lesson plan they made and the document stated clearly they stimulate students to be active. 2) Teachers have implemented various ALS methods such as Everyone Is A Teacher Here, Index Card Match, and Team Quiz so that the atmosphere created is fun, warm, and enthusiastic. 3) To appreciate as well as encourage students to be engaged, teachers do not only assess the cognitive aspects of students but extend the range of evaluation to the affective and psychomotor domains using Behaviour-based Evaluation so that all processes are taken into account.